Sustainable property financing for Malaysia Madani - Hassan, Hasroleffendy; Abu Hassan, Mohamad Hanif; Othman, Muhammad Hanif (2023)
Albeit the fourty years’ existence of Islamic property financing in Malaysia, it has yet to fully achieve its real objectives in social justice and sustainability. Being one of its key founders, Malaysian Prime Minister; Datuk Seri Anwar Ibrahim (PMX) highlighted in recent Malaysian 2023 budget that Islamic financial sector has not attained its full value-based capabilities to meet current economic and social needs, particularly socio-economic development and morality. Additionally, there are still numerous perceptions among Muslims that Islamic property financing in Malaysia is just akin to its conventional version with only conversion of terms and contracts to be Islamic with similar cost or more expensive than conventional financings. There have been several negative comments by Islamic jurists and industry observers on Islamic property financing in Malaysia but there are scarcely any better practical suggestions to improve the same towards sustainability and socio-economic development apart from competing with their conventional counterparts. Hence, this article underscores the shortcomings in Malaysia's Islamic property financing system concerning legality, social justice, and sustainability. This study proposed a more sustainable property financing package which suitable for all levels of people but shariah compliant yet could still contribute profits to the financiers/banks. This article proposes comprehensive improvements that align closely with Shariah principles as well as with Malaysia Madani aspirations. Highlights are on the salient features namely shariah viewpoints, legal transfer and documentation, repayment and selling price together with redemption and early settlement. Proposed enhancements are derived from practical experience and learning, bank insights and academic research. The practical implementation details are elaborated upon, whereby the practicability and potential positive impact of these enhancements underline the research's value in advancing authentic social welfare through financial avenues.